Mathematical Anxiety, Learning Motivation, and Mathematical Creative Thinking in Junior High School - Kristiarta, Yosafat Ardian; Saputro, Totok Victor Didik; Nugraha, Adhi Surya; Marsigit, Marsigit; Wulanningtyas, Melania Eva (JagoMIPA: Jurnal Pendidikan Matematika dan IPA, 2025)
This study contains the effect of mathematical anxiety on the motivation to learn mathematics and the mathematical creative thinking abilities of junior high school students. Mathematics learning also needs to understand the psychological aspects of students, including about mathematical anxiety and motivation to learn mathematics. Mathematical anxiety and motivation to learn mathematics that are not immediately addressed properly and correctly will affect students' creative thinking skills in mathematics. The purpose of this study was to determine the effect of mathematical anxiety on learning motivation and mathematical creative thinking abilities of junior high school students. This study uses the literature review method with publication limitations of the last 5 years. Exploration of publication results using an open-access website taken from Google Scholar with research results published in Reputable National Journals at least Sinta 4 and Reputable International Journals at least Q3. Publication results are limited to searches using the keywords “Math Anxiety”, “Learning Motivation”, “Creative Thinking Skills”, “Junior High School Mathematics Learning”, “Math Anxiety”, “Learning Motivation”, “Creative Thinking Skills”, and “Mathematics Learning in Junior High School”. Exploration results of publications were analyzed using PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) syntax. The results showed that mathematical anxiety had an effect on motivation to learn mathematics and students' mathematical thinking abilities. Students who have excessive mathematical anxiety tend to have low motivation to learn mathematics. Low motivation to learn mathematics will affect the way students think, especially with regard to the ability to think creatively mathematically. Therefore, teachers must be alert and communicative in order to overcome these problems and students become more comfortable when learning mathematics.